PENERAPAN METODE PICTURE AND PICTURE DALAM KETERAMPILAN MENULIS NASKAH DRAMA ANAK - FAQIH, FIYAN ILMAN (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
The skill of writing children's drama script must be in accordance with all children's lives. These skills are not easy for adults. Adults tend to force their minds on children. This happens because adults find it hard to think like children. This study aims to describe the application of the picture and picture method in writing children's drama scripts. There are 5 aspects that must be considered in writing children's drama scripts: uniqueness, creativity, interest, level of children's development, and the position of the drama script in the lives of children. These five aspects are the basis in the creation of ideas, themes, mandates, characters, disposition, setting, and plot of the children's drama script. These five aspects appear in the picture and picture method. The method can record all the activities of children so that children's drama scripts according to the uniqueness, creativity, interests, and level of development of children.